A new species of Phrynobatrachus (Amphibia: Anura: Phrynobatrachidae) from the Northern Mountains of Tanzania. Issue 1 (17th January 2020) - Greenwood, Laura; Loader, Simon P.; Lawson, Lucinda; Greenbaum, Eli; Zimkus, Breda M.
ABSTRACT: Using integrative approaches, a new large-bodied species of Phrynobatrachus is described from a series of 48 specimens from the montane forests of the West Usambara and North Pare Mountains of Tanzania. The most distinguishing morphological feature separating Phrynobatrachus ambanguluensis sp. nov from similar species is the markedly overhanging and pointed upper jaw and snout. Mitochondrial 16S rRNA indicates that the new species differs from all other species with published sequence data by a minimum distance of 4.75% and is sister to P. krefftii, with which it has been confused in the past. The new species is known from two forest reserves and is of high conservation concern given these areas are highly impacted by anthropogenic change. http://www.zoobank.org/urn:lsid:zoobank.org:pub:E0C82A87-47A5-426B-978D-96D27FA7A3B7